Evaluation of the Antioxidative Properties of N-Acylamino-Substituted Tricyclic Imides - Melek Gul; Irem Kulu; Aysegul Peksel; Nuket Ocal (Journal of Chemistry)
New N-acylamino-substituted tricyclic imides have been screened for scavenging ability against the free radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH•), chelating activity on ferrous ions, and reductive potential. The results were compared with synthetic antioxidants BHT, BHA, and Trolox. The compounds exhibited different levels of antioxidant activity in all tests.